2020
DOI: 10.1007/s00035-020-00241-8
|View full text |Cite
|
Sign up to set email alerts
|

Dominant shrub species are a strong predictor of plant species diversity along subalpine pasture-shrub transects

Abstract: Abandonment of pastures and successional shrub expansion are widespread in European mountain regions. Moderate shrub encroachment is perceived beneficial for plant diversity by adding new species without outcompeting existing ones, yet systematic evidence is missing. We surveyed vegetation along 24 transects from open pasture into shrubland across the Swiss Alps using a new protocol distinguishing different spatial scales, shrub cover of each plot (2 × 2 m) and larger-scale zonal cover along the transect. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
4
18
0
Order By: Relevance
“…Overall, plant communities with higher A. viridis cover had lower plant diversity and were dominated by a few broad-leaved species, like A. alliariae and C. alpina, which prefer N-enriched conditions. These results support the findings of Anthelme et al (2001) and Zehnder et al (2020), who also showed a decline in alpine plant diversity with A. viridis encroachment. The few species that survive in A. viridis-dominated areas are able to take advantage of the N-enrichment and increased shading, and they replace many typical pasture species that are highly light demanding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Overall, plant communities with higher A. viridis cover had lower plant diversity and were dominated by a few broad-leaved species, like A. alliariae and C. alpina, which prefer N-enriched conditions. These results support the findings of Anthelme et al (2001) and Zehnder et al (2020), who also showed a decline in alpine plant diversity with A. viridis encroachment. The few species that survive in A. viridis-dominated areas are able to take advantage of the N-enrichment and increased shading, and they replace many typical pasture species that are highly light demanding.…”
Section: Discussionsupporting
confidence: 91%
“…Encroachment by A. viridis can have several negative agri-environmental impacts: in particular, A. viridis-dominated shrublands have lower plant and animal diversity and forage quality than open grazed areas (Anthelme et al, 2001). A recent study showed that A. viridis encroachment resulted in a rapid decline in plant species richness, with dense A. viridis patches hosting 62% less species than adjacent open pastures (Zehnder et al, 2020). Moreover, there is high nitrate and dissolved organic carbon leaching from A. viridis shrublands, which results in water pollution, soil acidification, hydrological drawbacks, and gaseous nitrogen losses (Bühlmann et al, 2016;van den Bergh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the vegetation surveys we recorded a total of 157 vascular species in the whole grazed surface of Ombretta, with a maximum of 49 and a minimum of 23 species per survey. This number was in line with what was found in other studies involving alpine pastures at the same altitude 88 , 89 , while the total number of species was higher. This is expectedly due to the spatial heterogeneity within the pasture area that increased species richness 90 , 91 .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to other shrub species, A. viridis fixes atmospheric nitrogen (N) by a mutualistic relationship with actinomycete Frankia alni . Thus, its expansion into subalpine grasslands has far‐reaching consequences for these initially nitrogen‐poor ecosystems and the wider environment: Due to the high N supply, A. viridis and a few fast‐growing understorey species, such as Adenostyles alliariae or Peucedanum ostruthium , out‐compete most other plant species and thus, biodiversity declines tremendously (Anthelme et al, 2003) and clearly more than with other shrub species (Zehnder et al, 2020). While N leaching in open pastures is close to zero, surplus N continuously leaches from A. viridis stands (Bühlmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%